Hubungan Tingkat Pengetahuan Ibu Tentang Inisiasi Menyusu Dini dan Status Pekerjaan Ibu dengan Status Pemberian ASI di Kecamatan Jatipuro Kabupaten Karanganyar - Malitasari, Ratna, Endang Nur Widyaningsih, S.ST.,M.Si,Med, Rustiningsih, SKM., M.Kes (2013)
Background : Breast Milk (ASI) is the best food for babies because it contains the appropriate nutrients for growth and development of infants. But in reality the scope of exclusive breastfeeding in Indonesia is still low. The main problem of low coverage exclusive breastfeeding is the socio-cultural factors, lack of knowledge in Early Initiation of Breastfeeding (IMD), maternal employment status and the promotion of infant formula. Objective : Determine the correlation between maternal knowledge about IMD and mother employment status with exclusive breastfeeding in the District Jatipuro Karanganyar. Research Method : This study is an observational study with cross sectional method. Samples were 70 mothers having 7-12 month babies in the District Jatipuro. The instrument used in this study were interviews with reference questionnaire. The hypothesis test used is the Chi-Square test. Result : Mothers with good level of knowledge IMD 68.9% exclusive breastfeeding for babies and mothers with less than 64% of the level of knowledge does not give exclusive breastfeeding their babies. 65.4% of the working mother does not give exclusive breastfeeding for baby and mother are not working or housewives 70.5% exclusive breastfeeding their babies. Conclusion : Chi-Square test results test showed a correlation between maternal knowledge about IMD with exclusive breastfeeding (p-value = 0.008; CC = 0303) and there is a relationship between maternal employment status with exclusive breastfeeding in the District Jatipuro Karanganyar (p-value = 0.003 ; CC = 0330).